A.) Your first EXPRESSION (not "equation") simplifies to
2 cot (2θ).
B.) The expression in your "Additional details" (which are NOT additional details, but rather IS a completely separate, additional question) simplifies to (1/4) sin^2 (2θ).
These separate simplifications are done as follows:
A.) : (sec θ + csc θ) (cos θ - sin θ)
= (1 / cos θ + 1 / sin θ) (cos θ - sin θ)
= 1 + cos θ / sin θ - sin θ / cos θ - 1
= (cos^2 θ - sin^2 θ) / (sin θ cos θ)
= cos (2θ) * 2 / sin (2θ) = 2 cot (2θ).
B.) : (cos^2 θ * sin^2 θ) = (sin θ * cos θ)^2 = (1/4) sin^2 (2θ).
QED
Live long and prosper.
2007-03-17 06:23:20
·
answer #1
·
answered by Dr Spock 6
·
0⤊
0⤋
(secθ + cscθ) (cosθ - sinθ)
Changing everything to sines and cosines,
(1/cosθ + 1/sinθ) (cosθ - sinθ)
Using FOIL,
cosθ/cosθ - sinθ/cosθ + cosθ/sinθ - sinθ/sinθ
1 - sinθ/cosθ + cosθ/sinθ - 1
Note the cancellation.
-sinθ/cosθ + cosθ/sinθ
Now, putting this under a common denominator of sin(θ)cos(θ), we get
[-sin^2(θ) + cos^2(θ)] / [sin(θ)cos(θ)]
Rearranging the top,
[cos^2(θ) - sin^2(θ)] / [sin(θ)cos(θ)]
This is the part that requires intuition. By the double angle identity
cos(2θ) = cos^2(θ) - sin^2(θ)
sin(2θ) = 2sin(θ)cos(θ). For this equation, multiply both sides by (1/2), we get
(1/2)sin(2θ) = sin(θ)cos(θ)
Therefore,
[cos^2(θ) - sin^2(θ)] / [sin(θ)cos(θ)]
becomes
cos(2θ) / [ (1/2) sin(2θ) ]
Multiply top and bottom by 2,
2 cos(2θ)/sin(2θ)
Which, by definition, is equal to
2cot(2θ)
Side note: To avoid confusion in the future, remember to use the word "expression" instead of "equation" if there's no equal sign involved. I was initially confused when you declare an equation, but I could not find an equation.
2007-03-17 04:54:29
·
answer #2
·
answered by Puggy 7
·
1⤊
1⤋
(sec x + cosec x)(cos x - sin x)
= (1/cos x + 1/sin x)(cos x - sinx)
= (sin x + cos x)(cos x - sin x)/(cos x sin x)
= (cos^2 x - sin^2 x)/cos x sin x
= 2(cos 2x) / sin 2x
= 2cot(2x)
I'm afraid I don't understand how you arrived at your division by 0.
2007-03-17 05:13:13
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
sorry i replaced the attitude theta with the help of x,yet you recognize that no longer something replaced . csc x=a million/sinx and sec x=a million/cos x then (sinx/csc x)+(cos x/sec x)=(sinx/(a million/sin x))+(cosx(/a million/cosx))=sin^2x+cos^2x= a million
2016-10-18 22:18:13
·
answer #4
·
answered by ? 4
·
0⤊
0⤋
(cos^2x * sin^2x) = cos^2xsin^2x = (sinxcosx)^2 = 1/4 (sin2x)^2
2007-03-17 04:55:39
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
((1/cos t)+(1/sin t))(cos t) - ((1/cos t)+(1/sin t))(sin t)
1+(cos t)/(sin t)-((sin t)/(cos t)+1)
1+(cot t)-(tan t)-1
cot t - tan t
2007-03-17 04:55:58
·
answer #6
·
answered by sdenison1983 3
·
1⤊
0⤋